Comparative study between the structural and tectonic situation of the Southern Sinai and the Red Sea, Egypt, as deduced from magnetic, gravity and seismic data - EL-BOHOTY, Mohamed; BRIMICH, Ladislav; SALEH, Ahmed; SALEH, Salah (Contributions to Geophysics and Geodesy, 2012)
The present study is concerned with the analysis of magnetic gravity and seismic data for the regions of the South Sinai and the Red Sea areas aiming to evaluate the subsurface geologic active structures. The magnetic method of prospecting gives an effective presentation of the subsurface structures. Moreover, the wavenumber filtering is carried out utilizing three types of filters with varying wavelengths. The application of these tools on the magnetic and gravity data discriminated the variable sources of specific depth ranges for the residual and regional anomalies, as well as those limited to a certain depth interval. Also it was found that the main tectonic trends have taken the NE–SW and NW–SE directions. A three-dimensional (3D) interpretation of the Bouguer anomaly and aeromagnetic maps of the Gulf of Suez rift and the northern part of the Red Sea rift are presented. A high-resolution 3D model constrained with the seismic results reveals a possible crustal thickness and density distribution of the north Red Sea rift between the sedimentary cover and the mantle.